2013
DOI: 10.1128/mcb.00895-13
|View full text |Cite
|
Sign up to set email alerts
|

Activated Cdc42-Bound IQGAP1 Determines the Cellular Endocytic Site

Abstract: dRecruitment of specific molecules to a specific membrane site is essential for communication between specialized membranous organelles. In the present study, we identified IQGAP1 as a novel GDP-bound-Rab27a-interacting protein. We found that IQGAP1 interacts with GDP-bound Rab27a when it forms a complex with GTP-bound Cdc42. We also found that IQGAP1 regulates the endocytosis of insulin secretory membranes. Silencing of IQGAP1 inhibits both endocytosis and the glucose-induced redistribution of endocytic machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…These interactions are important for the transport and tethering of insulin granules. We recently identified coronin 3 (also known as CORO1C) and IQGAP1 as new Rab27a-interacting proteins (Kimura et al, 2008(Kimura et al, , 2013. In contrast to previously established small GTPase interactors, these proteins selectively form a complex with the GDP-bound, but not with the GTP-bound, Rab27a.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These interactions are important for the transport and tethering of insulin granules. We recently identified coronin 3 (also known as CORO1C) and IQGAP1 as new Rab27a-interacting proteins (Kimura et al, 2008(Kimura et al, , 2013. In contrast to previously established small GTPase interactors, these proteins selectively form a complex with the GDP-bound, but not with the GTP-bound, Rab27a.…”
Section: Introductionmentioning
confidence: 98%
“…We have demonstrated previously that GDP-bound Rab27a promotes glucose-induced clathrin-dependent endocytosis through its interaction with coronin 3 and IQGAP1 (Kimura et al, 2008(Kimura et al, , 2013. We therefore examined the effect of the crosstalk between EPI64 and ARNO signaling on endocytosis.…”
Section: Arno Is Required For the Glucose-induced Translocation Of Epi64mentioning
confidence: 99%
“…[34][35][36][37][38][39][40] We recently identified IQGAP1 as another GDP-dependent Rab27a effector. 41) GDP-bound Rab27a interacts with IQGAP1 via its RasGAP related domain (GRD). This domain is a part of the GTP-bound Cdc42-binding region of IQGAP1.…”
Section: Iq Motif Containing Gtpase Activating Protein 1 (Iqgap1)mentioning
confidence: 99%
“…Studies on β-cells have revealed that IQGAP1 recruits the endocytic machinery to the plasma membrane together with GTP-bound Cdc42 [125] and that IQGAP1-exocystseptin enhanced exocytosis is inhibited by Cdc42 [126]. In adherens junction fractions from rat liver Rac-Cdc42-IQGAP1 was shown to inhibit the clathrin-dependent (caveolae-independent) endocytosis of E-cadherin, probably through cross-linking of Factin [127].…”
Section: Iqgap1 and The Cytoskeletonmentioning
confidence: 99%